2003
DOI: 10.1046/j.1538-7836.2003.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein (MGP) and bone morphogenetic protein-2 in aortic calcified lesions of aging rats

Abstract: Summary. The vitamin K-dependent protein, matrix Gla protein (MGP) is a binding protein for bone morphogenetic protein-2 (BMP-2). Here we present additional evidence that the Ca 2þ -induced conformer of the vitamin K-dependent Gla region in MGP is involved in BMP-2 binding. Recombinant BMP-2 binds to the Gla-containing region of MGP in the presence of Ca 2þ . Immunohistochemistry showed that calcified lesions in the aortic wall of aging rats contained elevated concentrations of MGP that was poorly g-carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 20 publications
6
129
0
3
Order By: Relevance
“…This can be seen in Figures 2 and 3 in which the majority of the newly synthesized MGP is produced in the undercarboxylated, inactive form. This is in agreement with work from Sweatt et al 13 who showed that in aging rats ucMGP was associated with arterial calcification as demonstrated with polyclonal conformation-specific MGP antibodies. The researchers concluded that inactive MGP because of vitamin K deficiency could lead to arterial calcifications.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This can be seen in Figures 2 and 3 in which the majority of the newly synthesized MGP is produced in the undercarboxylated, inactive form. This is in agreement with work from Sweatt et al 13 who showed that in aging rats ucMGP was associated with arterial calcification as demonstrated with polyclonal conformation-specific MGP antibodies. The researchers concluded that inactive MGP because of vitamin K deficiency could lead to arterial calcifications.…”
Section: Discussionsupporting
confidence: 93%
“…MGP acts by direct inhibition of calcium crystal formation and regulates bone morphogenetic protein-2, a growth factor responsible for osteogenic differentiation. [11][12][13] Murshed et al 14 demonstrated that restoration of MGP exclusively in the vascular smooth muscle cells of the MGP-null mice completely rescued the vascular calcification phenotype. For this effect the MGP needed to be ␥-carboxylated because mutating the Gla residues into aspartic acid residues led to the synthesis of nonfunctional MGP and to the death of all animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the hypothesis that the Gla region in MGP indeed is involved in BMP-2 binding and regulation of the ostergenic growth factor activity of BMP-2. The data also add support to our earlier finding that overexpression of non γ-carboxylated MGP in calcified lesions in the aorta of aging rats results in unopposed BMP-2 activity which may contribute to osteoblastic differenation of cells laying down the observed calcified matrix (29). BMP-2 at 5 nM was used in all experiments and significantly higher concentrations of the Gla-and the Glu-MGP peptides were needed to measure significant inhibitory effects.…”
Section: Discussionsupporting
confidence: 84%
“…tein-protein interaction between BMP-2 and MGP (20,53,54) and modulation of BMP-2 activity (19 -21). Alternatively, it may target specific ligand-receptor complexes analogous to endoglin (55) or betaglycan (56), or it may alter the balance between signaling through the canonical Smad pathway and other, non-canonical signaling pathways (25).…”
Section: Figmentioning
confidence: 99%